Electrochemical and Spectroscopic Study of Homo‐ and Hetero‐Dimetallic Phthalocyanines as Catalysts for the Oxygen Reduction Reaction in Acidic Media. Issue 22 (19th September 2018) - Wang, Xiaojiang; Liu, Yang; Wang, Ying; Ren, Rong; Chen, Hengquan; Jiang, Zheng; He, Qinggang
Abstract: Metallophthalocyanines (MPc, M=Fe or Co) have been investigated extensively as a typical type of transition metal macrocyclic catalysts for the oxygen reduction reaction (ORR). However, the understanding about ORR catalyzed by binuclear even heterodimetallic phthalocyanines in acidic condition is still not sufficient. Herein we synthesized two homodimetallicphthalocyanine (FePc‐PcFe and CoPc‐PcCo) and a heterodimetallic phthalocyanine (FePc‐PcCo). The electrocatalytic activity of as‐synthesized compounds were characterized by cyclic voltammetry (CV) and rotating disk electrode (RDE). Generally, the binuclear metallophthalocyanines show higher activity than their monomeric analogues including FePc and CoPc. Also, the Fe compounds exhibit better catalytic performance than the Co phthalocyanines. However, interestingly the heterodimetallic phthalocyanine FePc‐PcCo shows similar half‐wave potential and ORR activity with FePc‐PcFe, rather than CoPc‐PcCo. This may be explained by XPS and XAS, which reveal a similar square‐planar structure existed in FePc‐PcCo and FePc‐PcFe and a non‐planar structure in CoPc‐PcCo. Furthermore, the increasing of the ORR activity among those five catalysts is well in agreement with the descending LUMO energies in DFT calculations. A lower LUMO energy indicates a favorable adsorption of O2, which in turn affects the ORR performance. Abstract : Orthrus catalysts : two homodimetallic phthalocyanines (FePc‐PcFe and CoPc‐PcCo) and a heterodimetallicphthalocyanine (FePc‐PcCo) are studied as catalysts for the oxygen reduction reaction. Interestingly the heterodimetallic phthalocyanine FePc‐PcCo shows similar activity with FePc‐PcFe, rather than CoPc‐PcCo. XPS, XAS as well as DFT calculations are applied to explain this phenomenon.